Analysis of Health Related Financial Flows and Patient Satisfaction with Private Health Care in the Czech Republic - Supová, Aneta (2016)
This Master Thesis focuses on the structure of health related financial flows and patient satisfaction with privately owned hospitals in the Czech Republic. The main aim was to provide a general overview of health care system in the Czech Republic, to describe how the health care system is financed, and to find out if patients hospitalized in privately owned hospitals are more satisfied with the care provided in this type of hospitals. Having analyzed the major statistical reports from the WHO, EU, and the Institution of Health Information and Statistics of the Czech Republic, the theoretical part provided a comprehensive summary of health care, health financial flows, and pricing of health treatments. The practical part, on the other hand, shows distribution of health costs among differently aged people in the form of contribution/expenditure ratio. Finally, the results of the questionnaires conducted among patients in privately owned hospitals enabled to conclude that patients in the Czech Republic are still not fully aware of the difference between privately and publically owned hospitals.